2022
DOI: 10.3390/ijerph192114448
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and COVID Experience Predictors of COVID-19 Risk Perception among Chinese Residents in Canada

Abstract: The current study aimed to identify demographic and COVID experience predictors for COVID-19 risk perception among Chinese residents in Canada. A final sample of 653 participants aged 18 and up completed an online survey in simplified Chinese during the peak of the first wave of COVID-19 (25 April–10 June 2020). After removing those with missing data on demographic covariates, as missing data cannot be imputed, 444 were included in the structural equation model, and COVID-19 risk perception was indexed by thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Consistently, Statistics Canada found that reports of racially based attacks and forms of harassment against Chinese Canadians increased by 30% from the onset of the pandemic to May 2020 [19,20]. Our past work also identified discrimination (perceived or experienced) as a robust and strong risk factor for COVID-19-related risk perceptions [21] as well as mental health outcomes among Chinese Canadians during the pandemic [10,[22][23][24]. Increased incidences of racial discrimination, reports of higher anxiety symptoms among immigrant populations, and the cultural barriers/stigma around accessing mental health support make it essential to understand the risk factors for this population [10].…”
Section: Chinese Canadian Populationsupporting
confidence: 69%
“…Consistently, Statistics Canada found that reports of racially based attacks and forms of harassment against Chinese Canadians increased by 30% from the onset of the pandemic to May 2020 [19,20]. Our past work also identified discrimination (perceived or experienced) as a robust and strong risk factor for COVID-19-related risk perceptions [21] as well as mental health outcomes among Chinese Canadians during the pandemic [10,[22][23][24]. Increased incidences of racial discrimination, reports of higher anxiety symptoms among immigrant populations, and the cultural barriers/stigma around accessing mental health support make it essential to understand the risk factors for this population [10].…”
Section: Chinese Canadian Populationsupporting
confidence: 69%